Structural and functional state of the skin microcirculation in men with different phenotypes of hypertension of low and moderate cardiovascular risk - A. I. Korolev; V. S. Ososkov; A. A. Fedorovich; M. G. Chashchin; V. A. Dadaeva; A. V. Strelkova; K. V. Omelyanenko; M. A. Mikhailova; A. Y. Gorshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To study the structural and functional state of skin microcirculation in working-age men with different phenotypes of hypertension (HTN) of low/moderate cardiovascular risk.Material and methods. A total of 218 healthy men underwent total blood count and biochemical blood tests, volumetric sphygmography, videocapillaroscopy, laser Doppler flowmetry at rest and with constrictor and dilator tests, photoplethysmography, flow-mediated vasodilation of the brachial artery, cardiac and main artery ultrasound, 24-hour blood pressure (BP) monitoring. Based on the 24-hour BP monitoring, three following groups were formed: normal BP (NBP) group — 72 men, isolated diastolic hypertension (IDH) group — 70, systolic-diastolic hypertension (SDH) group — 76.Results. According to videocapillaroscopy and laser Doppler flowmetry, no reliable intergroup differences were found at the level of capillaries and precapillary arterioles. According to photoplethymography, men with SDH compared to the NBP group had higher AIp75 (augmentation index normalized to 75 bpm) (7,35 vs -5,4%; p<0,001), vascular age (VA) (49 vs 43 years; p<0,001) and reflection index (RI) (38 vs 29,1%; p<0,001), while patients with IDH had higher RI (35,3 vs 29,1%; p<0,001), respectively.Conclusion. Men with IDH and SDH do not have capillary rarefaction, tone changes, or constrictor and dilator activity of skin precapillary arterioles. Men with IDH and SDH are characterized by a higher tone of smooth muscle cells of terminal muscular arteries and distributing arterioles, and men with SDH also have higher arterial stiffness.